Environmental protests in Europe - Borbáth, Endre; Hutter, Swen (Journal of European public policy, 2024)
Despite growing attention to the resurgence of environmental, and especially climate-related mobilisation in Europe, comparative assessments across countries and over time are lacking. Using classic social movement theories (grievances, opportunities, resources), we examine the frequency, profile, and drivers of environmental protest. We conduct a two-step analysis based on the updated PolDem protest event dataset covering 27 European countries from 2000 to 2021. We move from descriptive accounts to dynamic regressions, modelling the cross-national and temporal variation in the number of environmental protests, the participants involved, and their share of all events. The results highlight 2019 as pivotal for environmental protests, with a peak in participants and heightened salience in Europe's protest landscape. Typical environmental protests are well-attended, symbolic, and confrontational actions, exclusively focussed on the issue, and draw support from both professional and non-professional organisations. Temporal variation in the number and share of environmental protests is related to proxy measures for resources in the environmental field, while participation rates correlate with political opportunities as measured by governments' positions on environmental protection. Thus, the simultaneous presence of opportunities and resources tends to create an ‘explosive mix’, fuelling environmental protest dynamics.
Gesehen am 26.09.2024